Fabrication and evaluation of porous hydroxyapatite for medical applications - Yang, Hai Yong (2008)
Porous hydroxyapatite, Caio(P04)6(OH)2, is a promising bioactive material for bone substitution and guided tissue growth. In this investigation, a comprehensive study was conducted on the production and evaluation of porous hydroxyapatite (HA) with controlled pore characteristics. The work started with HA ceramic powder preparation, proceeded onto manufacturing ceramic parts employing three different processing routes and various sintering regimes, and finished with the evaluation of sintered products.